Dysregulated B cell function and disease pathogenesis in systemic sclerosis - Beesley, Claire F.; Goldman, Nina R.; Taher, Taher E.; Denton, Christopher P.; Abraham, David J.; Mageed, Rizgar A.; Ong, Voon H. (Frontiers in Immunology, 2023)
Systemic sclerosis (SSc) is a complex, immune-mediated rheumatic disease characterised by excessive extracellular matrix deposition in the skin and internal organs. B cell infiltration into lesional sites such as the alveolar interstitium and small blood vessels, alongside the production of defined clinically relevant autoantibodies indicates that B cells play a fundamental role in the pathogenesis and development of SSc. This is supported by B cell and fibroblast coculture experiments revealing that B cells directly enhance collagen and extracellular matrix synthesis in fibroblasts. In addition, B cells from SSc patients produce large amounts of profibrotic cytokines such as IL-6 and TGF-β, which interact with other immune and endothelial cells, promoting the profibrotic loop. Furthermore, total B cell counts are increased in SSc patients compared with healthy donors and specific differences can be found in the content of naïve, memory, transitional and regulatory B cell compartments. B cells from SSc patients also show differential expression of activation markers such as CD19 which may shape interactions with other immune mediators such as T follicular helper cells and dendritic cells. The key role of B cells in SSc is further supported by the therapeutic benefit of B cell depletion with rituximab in some patients. It is notable also that B cell signaling is impaired in SSc patients, and this could underpin the failure to induce tolerance in B cells as has been shown in murine models of scleroderma.